Magnetostratigraphy of sediment core PS115/2_2 - Ruediger Stein; Thomas Frederichs; Kirsten Fahl; Walter Geibert; Jens Matthiessen; Frank Niessen; Christoph Vogt; Cynthia Sassenroth; Evgenia A Bazhenova (PANGAEA, 2025)
Sediment Core PS115/2-2 was recovered from the Amundsen Basin in 3600 m water depth at the eastern flank of the Gakkel Ridge during Polarstern Expedition PS115/2 in 2018 (Stein, 2019). The well-dated core is used to reconstruct in detail the interrelationship between ice-sheet dynamics and organic carbon burial in the central Eurasian Basin during the last 430 kyr, and to correlate marine and terrestrial records of the Eurasian Ice Sheet (EIS) history. Our age model, a fundamental prerequisite for any kind of paleoclimatic reconstruction, is based on magnetostratigraphy, 230Th and 231Pa excess (230Thex and 231Paex) records, and AMS14C ages. For magnetostratigraphy, we have determined records of the inclination and relative paleointensity (RPI) of the Earth extquotesingles magnetic field, combined with rock magnetic measurements to assess a possible diagenetic overprint on the paleomagnetic signal (cf., Frederichs, 1995; Tauxe et al., 1995; Channell et al., 2009, 2020). For details and methods, we refer to Stein et al. (this paper).
In: Stein, R et al. (2025): A 430 kyr multi-proxy record of Eurasian Ice Sheet history and organic carbon burial in the eastern Eurasian Basin, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.975790